2012
DOI: 10.1007/s10493-012-9545-x
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal activity and repellency of essential oil from Piper aduncum and its components against Tetranychus urticae

Abstract: The chemical composition of essential oil of leaves of Piper aduncum L., growing wild in a fragment of the Atlantic Rainforest biome in northeastern Brazil, was determined through gas chromatography-mass spectrometry. The acaricidal activity and repellency of the essential oil and its components [dillapiole (0.28 g/ml), α-humulene (0.016 g/ml), (E)-nerolidol (0.0007 g/ml) and β-caryophyllene (0.0021 g/ml)] were evaluated in the laboratory against adults of Tetranychus urticae Koch. The mites were more suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 27 publications
5
51
1
Order By: Relevance
“…Among the major components, only β-caryophyllene and patchoulol, which were found in different proportions in stem, flower, and leaf oils, and it demonstrated acaricidal activity. The biological properties of β-caryophyllene have been confirmed in previous reports involving the larvae of Aedes aegypti (Diptera: Culicidae) (Dória et al, 2010) and T. urticae (Araújo et al, 2012). Moreover, the major constituents are not the only components responsible for the fumigating action observed in the experiments and it is likely that these compounds act in synergy with those found in smaller amounts .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Among the major components, only β-caryophyllene and patchoulol, which were found in different proportions in stem, flower, and leaf oils, and it demonstrated acaricidal activity. The biological properties of β-caryophyllene have been confirmed in previous reports involving the larvae of Aedes aegypti (Diptera: Culicidae) (Dória et al, 2010) and T. urticae (Araújo et al, 2012). Moreover, the major constituents are not the only components responsible for the fumigating action observed in the experiments and it is likely that these compounds act in synergy with those found in smaller amounts .…”
Section: Discussionsupporting
confidence: 82%
“…This is the first report of the fumigating action of P. marginatum oils on T. urticae and its natural enemy N. californicus. However, the evaluation of the acaricidal activity of other plant species against T. urticae has been investigated previously, such Protium bahianum, Protium heptaphyllum (Pontes et al, 2007a;, Xylopia sericea (Pontes et al, 2007b), Citrus sinensis, Citrus aurantium (Araújo-Júnior et al, 2010), and Piper aduncum (Araújo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jantan & Zaki (1998) reported that formulations made of Cinnamomum camphora Linnaeus (Lauraceae), Mentha pulegium Linnaeus (Labiatae) essential oils and camphor components had long-term repellent effects against pests, and some monoterpenoids such as α-pinene, limonene, terpinolene, citronellol, citronellal and camphor also had repellent effects. Araujo et al (2012) reported that Piper aduncum essential oil and its principle components (nerolidol, α-humulene and β-caryophyllene) did not show a repellent effect in T. urticae. Conclusive research has shown geraniol to be an effective plant-based mosquito repellent and an insecticide for controlling pests with low mammalian toxicity and biodegradability (Omolo et al, 2004;Chen & Viljoen, 2010).…”
Section: Discussionmentioning
confidence: 99%